Edukasi dan Deteksi Dini Kadar HDL dan Kolesterol dalam Rangka Menjaga Kualitas Kesehatan pada Populasi Lansia di Panti Werda Hana - Limas, Peter Ian; Santoso, Alexander Halim; Gunaidi, Farell Christian; Teguh, Stanislas Kotska Marvel Mayello; Gracienne Gracienne (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2025)
Hypercholesterolemia is one of the health problems that is often experienced by the elderly and has a major impact on their quality of life, especially because it increases the risk of cardiovascular diseases such as coronary heart disease, stroke, and peripheral vascular disorders. This condition often does not show symptoms, but the process of atherosclerosis can develop slowly and cause serious complications if not treated early. The Community Service Program (PKM) implemented at Panti Werdha Hana aims to increase awareness among the elderly of the importance of early detection of Cholesterol and High Density Lipoprotein (HDL) levels as part of efforts to prevent heart disease. This activity applies the Plan-Do-Check-Act (PDCA) approach, including total cholesterol and HDL examinations using the Point-of-Care Testing (POCT) method, as well as interactive education about risk factors and healthy lifestyles. The results of the activity showed that out of 76 participants, 38 people (50%) had total cholesterol levels above normal, while 22 people (28.95%) had low or very low HDL levels. Early detection through screening has proven effective in identifying cardiovascular risks earlier and providing a basis for timely medical and educational interventions. Through this activity, it is hoped that the elderly can understand their health conditions better and take preventive steps to maintain lipid levels within normal limits, to improve the quality of life and reduce the risk of cardiovascular complications in the future.